2004
DOI: 10.1897/03-609
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment polymers identified as the toxic component of a diamond mine effluent

Abstract: The Ekati Diamond Mine, located approximately 300 km northeast of Yellowknife in Canada's Northwest Territories, uses mechanical crushing and washing processes to extract diamonds from kimberlite ore. The processing plant's effluent contains kimberlite ore particles (< or =0.5 mm), wastewater, and two wastewater treatment polymers, a cationic polydiallydimethylammonium chloride (DADMAC) polymer and an anionic sodium acrylate polyacrylamide (PAM) polymer. A series of acute (48-h) and chronic (7-d) toxicity test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although poly(DADMAC) itself has been shown to be toxic towards aquatic organisms [22], many natural water-soluble polyelectrolytes could be spinlabeled and used as nontoxic polarizing agents (e.g., polysaccharides or chitosan derivatives). Furthermore, one can devise schemes to extract spin-labeled polyelectrolytes from the solutions before injection by using them as a fixed polyelectrolyte gel matrix (similar to the system in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Although poly(DADMAC) itself has been shown to be toxic towards aquatic organisms [22], many natural water-soluble polyelectrolytes could be spinlabeled and used as nontoxic polarizing agents (e.g., polysaccharides or chitosan derivatives). Furthermore, one can devise schemes to extract spin-labeled polyelectrolytes from the solutions before injection by using them as a fixed polyelectrolyte gel matrix (similar to the system in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The adding of soil could reduce toxicities of chitosan and cationic starch by one to two orders of magnitude. Some reports indicated that clays could effectively reduce the acute toxicities of cationic polymers to aquatic organisms (de Rosemond and Liber, 2004). Goodrich et al (1991) also found that the biotic toxicity of cationic polymer was reduced 33-to 75-fold at higher humic acid concentrations (Goodrich et al, 1991).…”
Section: Toxic Effects Of Chitosan and Cationic Starch Modified Soilmentioning
confidence: 99%
“…High molecular weight PAMs can be modified to develop non-ionic, anionic, or cationic properties for specific uses (Scott et al, 1996). However for environmental applications which are described in this article, anionic PAMs are preferred because of their extremely low aquatic toxicity compared to cationic forms (Hamilton et al, 1994;de Rosemond & Liber, 2004;Liber et al, 2005). Common anionic…”
Section: Polyacrylamide and Acrylamide In Flocculation Processes And mentioning
confidence: 99%
“…The use of flocculants enables to increase the recycling rate of process water and to decrease sludge volumes and thus the surface of settling ponds. Those ponds are open systems with possible exchanges into the near aquatic environment (water percolation towards soils and aquifers, water seepages in natural streams or rivers…), which can lead to the dissemination of flocculants into surface and groundwaters (de Rosemond & Liber, 2004;Liber et al, 2005). The question of flocculants safety is now arising as a new key-environmental issue.…”
Section: Introductionmentioning
confidence: 99%